A generalized constructive algorithm using insertion-based heuristics - Danilovic, Milos; Ilic, Oliver (Computers & operations research, 2016)
In this paper, a generalized constructive algorithm referred to as GCA is presented which makes it possible to select a wide variety of heuristics just by the selection of its arguments values. A general framework for generating permutations of integers is presented. This framework, referred to as PERMGEN, forms a link between the numbering of permutations and steps in the insertion-based heuristics. A number of arguments controlling the operation of GCA are identified. Features and benefits of the generalized algorithm are presented through the extension of the NEH heuristic, a successful heuristic solution approach of Nawaz, Enscore, and Ham for the permutation flowshop problem (PFSP). The goal of the experimental study is to improve the performance of the NEH heuristic on the PFSP. To achieve this goal, the space of algorithmic control arguments is searched for a combination of values that define an algorithm providing lower makespan solutions than NEH, in a linear increase of CPU time. Computational experiments on a set of 120 benchmark problem instances, originally proposed by Taillard, are performed to establish a more robust version of the original NEH constructive heuristic. The proposed procedures outperform NEH, preserving its efficiency and simplicity. •Systematic, inclusive, encompassing representation of constructive-based heuristics.•Established link between the numbering of permutations and steps in constructive heuristics.•Improvement of constructive heuristics using successive algorithm implementations.•Comprehensive study of the influence of arguments on the results quality.•Improving the quality of NEH heuristic solutions while maintaining its comparative advantages.